PENGARUH PENERAPAN SISTEM MANAJEMEN MUTU ISO 9001:2015 TERHADAP KINERJA KARYAWAN PT. NINDYA KARYA (Studi Kasus : Proyek Pembangunan Bendungan Pamukkulu Paket 2 Takalar Sulawesi Selatan) - Palalangan , Aprilian Rante; Thioritz, Stevy; Kalangi, Hendry Tanoto (Jurnal Media Teknik Sipil, 2024)
Global market competition requires companies to continue to innovate in an effort to improve their services. The reality on the ground shows that companies that are advanced and able to survive in intense competition are companies that have been able to produce products with certain standards which of course can be produced if the company has employees who are reliable in their fields. The application of ISO 9001:2015 in construction companies can be carried out by referring to the clauses in ISO 9001:2015. The goal is to improve employee performance in order to produce products with guaranteed quality, so as to increase the company's credibility.This study aims to determine the degree of conformity of the ISO 9001:2015 Quality Management System implementation and the effect of the ISO 9001:2015 quality management system implementation on employees. The analytical method used to analyze the results of distributing the questionnaires is simple regression analysis.The results of this study indicate that the level of implementation of the ISO 9001:2015 quality management system by PT. Nindya Karya in the Pamukkulu Dam Development Project Package 2 of 90.026% is included in the very good category (81% -100%) and the application of the ISO 9001: 2015 quality management system has a positive and significant effect of 61.3% on employee performance.